The Analysis of Russian Oil and Gas Reserves - Grama, Yulia (International Journal of Energy Economics and Policy, 2012)
This paper devotes to the analysis of Russian oil and gas reserves. Currently, Russia holds world’s leading positions in oil and gas supply, but there is uncertainty for how long the country would be able to maintain it. After analyzing the situation in this industry, studying oil and gas fields and governmental policy towards hydro carbonates production and supply in Russia, the author will provide her projection about the future development of Russian oil and gas supplies to the global market. Keywords: Russia; Oil and gas reserves; Energy supply; Energy policy JEL Classifications: Q31; Q47; Q48